Evaluasi alat pemadam api ringan di kantor induk PT. PLN (persero) unit induk transmisi Jawa bagian timur dan Bali - Arrochman, Muhammad Iqbal Fahdi; Sunaryo, Merry; Sahri, Moch; Ratriwardhani , Ratna Ayu (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Fire is an oxidation event involving fuel, oxygen, and energy sources that can cause property. The requirements and implementation of this method using scientific methods such as inspection sheets as a tool to help solve the analysis. The results of the study from a total of 49 APAR were examined. From the results of the inspection that has been carried out, it was found that the indicator of the need for APAR in each room is an excess number of APAR, this is not a problem, the condition of the APAR has been appropriate but there are some that are not appropriate, the maintenance of APAR is only a few APAR that are checked routinely. In conclusion, although the number and type of APAR in each room are adequate, suggestions are needed to improve APAR, installation signs, placement of APAR, and maintenance of APAR to ensure safety.